Getting health reform right : a guide to improving performance and equity - Roberts, Marc J. (Oxford University Press, 2004)
This book attempts to meet a critical need felt by analysts, researchers, and officials struggling with health-sector reform around the world. The authors synthesize diverse analytical methods and international experience to provide practical guidance on how to improve the performance of health-care delivery systems. With a focus on the health-care system as a means to an end--intended to improve the well-being of a nation's population--the books helps the reader develop effective strategies tailored to each nation's individual situation.